The making of the Drosophila mushroom body - Lin, Suewei (Frontiers in Physiology, 2023)
The mushroom body (MB) is a computational center in the Drosophila brain. The intricate neural circuits of the MB enable it to store associative memories and process sensory and internal state information. The MB is composed of diverse types of neurons that are precisely assembled during development. Tremendous efforts have been made to unravel the molecular and cellular mechanisms that build the MB. However, we are still at the beginning of this challenging quest, with many key aspects of MB assembly remaining unexplored. In this review, I provide an in-depth overview of our current understanding of MB development and pertinent knowledge gaps.